Technological and Quality Aspects of the Use of Innovative Inorganic Binders in the Production of Castings - Tomáš Obzina (MDPI AG, 2021)
The production of cores for the pre-casting of holes in castings places high demands on the quality of the molding mixtures used. For this reason, organic binders are still used to a large extent, which, although they meet the technological requirements, are a source of pollutant emissions during the production of castings. The current trend towards greening production is therefore looking for a suitable alternative in ‘green’ inorganic binders. Although for many decades standard inorganic binders could not be compared with organic resins in terms of technological properties, new inorganic binder systems are currently being developed that can largely eliminate these disadvantages, which include, in particular, significantly lower collapsibility and reclaimability, and lower mechanical strength values. Last but not least, the use of these binder systems may be limited by the technological parameter of shelf-life, which is the main focus of this study. The aim of this paper is to evaluate the influence of technological parameters of core production using a new generation of inorganic binder systems on their shelf-life. Shelf-life, defined as the change in mechanical strength and wear resistance as a function of exposure time in a given environment, is evaluated under different climatic conditions.